IMPLEMENTASI ALGORITMA AES (ADVANCE ENCRYPTION STANDARD) RIJNDAEL PADA APLIKASI KEAMANAN DATA - Prajuhana Putra, Agung; Herfina, Herfina; Maryana, Sufiatul; Setiawan, Andrian (JIPETIK:Jurnal Ilmiah Penelitian Teknologi Informasi & Komputer, 2020)
AES Rijndael algorithm is a modern cryptographic algorithm published by NIST (National Institute of Standards and Technology) in 2001 using block cipher mode and using symmetric keys. AES Rijndael as a substitute for DES (Data Encryption Standard) algorithm whose use began in 1977 and has ended. The length of the block cipher used is 128 bits and variations in key length are 128 bits, 192 bits and 256 bits. AES Rijndael's algorithm has a reliability that is the simplicity of the bytes transformation process so that it can streamline encryption and decryption, and has high security.Implementation of the AES Rijndael algorithm will be done on Android devices to secure digital files, which can be used for all types of file types. The parameters used in the analysis are testing of the encryption and decryption processing time, changes in size and bits of the encrypted and decrypted files, then proving the strength of the key length against the robustness of the AES Rijndael algorithm as a symmetric algorithm.